Analysis Of Solar Power Plants With A Capacity Of 100 Wp With Automatic Transfer Switch In The Energy Conversion Laboratory Of Semarang State Polytechnic - Suwarti, Suwarti; Aulia, Nur Fatowil; Wahyono, Wahyono; Prasetyo, Budhi; Hendrawati, Dwiana; Hermawan, Baktiyar Mei (Politeknik Negeri Semarang, 2024)
Solar energy is one of the renewable energy sourcesby utilizing the sun as its energy source. The planning of thePLTS uses an on-grid system, the system is still connected tothe PLN network. The system is used as a backup forelectricity flow. The system will work automatically when thePLN electricity flow is cut off by utilizing the AutomaticTransfer Switch (ATS) control system. The PLTS was tested bymeasuring the voltage, current, and input and output powerfor 5 days from 09.00-15.00 WIB with data collection every 60minutes. Then calculations were made to determine theefficiency of the PLTS. Calculations were also made of theenergy produced by the panels needed and produced by thelights ideally and actually. The results of the DC voltage andDC current tests on average at a load of 70 Watts produced bythe solar panel were 12.7 V and 2.41 A with a data collectionperiod of 7 hours, producing energy of 214.3 Wh andproducing the highest efficiency of 7.9% and the lowest 4.84%.